2011
DOI: 10.1098/rsbl.2011.0735
|View full text |Cite
|
Sign up to set email alerts
|

Incubation temperature affects multiple measures of immunocompetence in young wood ducks (Aix Sponsa)

Abstract: Parental effects play a vital role in shaping offspring phenotype. In birds, incubation behaviour is a critical parental effect because it influences the early developmental environment and can therefore have lifelong consequences for offspring phenotype. Recent studies that manipulated incubation temperature found effects on hatchling body composition, condition and growth, suggesting that incubation temperature could also affect energetically costly physiological processes of young birds that are important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 19 publications
5
82
1
3
Order By: Relevance
“…Our previous studies, using the same incubation temperature treatments as this study, have found that ducklings incubated at the lowest temperature have reduced physiological performance relative to ducklings incubated at the higher temperatures (Hepp et al 2006;DuRant et al 2010DuRant et al , 2011Hopkins et al 2011;S. E. DuRant, W. A. Hopkins, A. F. Wilson, and G. R. Hepp, unpublished manuscript).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies, using the same incubation temperature treatments as this study, have found that ducklings incubated at the lowest temperature have reduced physiological performance relative to ducklings incubated at the higher temperatures (Hepp et al 2006;DuRant et al 2010DuRant et al , 2011Hopkins et al 2011;S. E. DuRant, W. A. Hopkins, A. F. Wilson, and G. R. Hepp, unpublished manuscript).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has demonstrated that subtle changes in incubation temperature can greatly influence avian hatchling characteristics (Goth and Booth 2005;Hepp et al 2006;Olson et al 2008;DuRant et al 2010DuRant et al , 2011Hopkins et al 2011;S. E. DuRant, W. A. Hopkins, A. F. Wilson, and G. R. Hepp, unpublished manuscript).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, slight deviations above the recommended incubation temperatures are more detrimental to inovo development than similar deviations below those temperatures. High incubation temperatures have negative impacts on chick heart weight (Wineland et al, 2000;Leksrisompong et al, 2007;Lourens et al, 2007), on bone development (Oviedo-Rondon et al, 2009a, b;van der Pool et al, 2014), and on the immune system (DuRant et al, 2012), predisposing chicks to ascites, leg problems, and immune deficiencies, respectively.…”
Section: Incubation Temperaturementioning
confidence: 99%
“…For example, in captive mice, several studies have shown wound healing to be a highly heritable trait (McBrearty et al, 1998;Li et al, 2001). Alternatively, DuRant et al (DuRant et al, 2012) demonstrated that the environment can also contribute to immunity independent of genetic contributions: ducklings incubated at sub-optimal temperatures showed a 19-21% decreased swelling response after injection with phytohaemagglutinin. Therefore, we recommend future studies be directed at understanding the relative contribution of parental and environmental factors on offspring immunity.…”
Section: Discussionmentioning
confidence: 99%